A case report of Neisseria mucosa peritonitis in a chronic ambulatory peritoneal dialysis patient - Alan Awdisho; Rafia Zulfikar (MDPI AG, 2017)
Peritonitis is a leading complication of chronic ambulatory peritoneal dialysis. However, very rarely does Neisseria mucosa cause peritonitis. We describe an unusual case of N. mucosa peritonitis in a chronic ambulatory peritoneal dialysis patient. A 28-year-old Hispanic male presents with diffuse abdominal pain exacerbated during draining of the peritoneal fluid. Peritoneal fluid examination was remarkable for leukocytosis and gramnegative diplococci. Bacterial cultures were positive for N. mucosa growth. The patient was treated with ciprofloxacin with preservation of the dialysis catheter. This case highlights the rarity and importance of Neisseria mucosa causing peritonitis in chronic ambulatory peritoneal dialysis patients'. There seems to be a unique association between N. mucosa peritonitis and chronic ambulatory peritoneal dialysis patients'. The patient was successfully managed with ciprofloxacin along with salvaging of the dialysis catheter.